1997
DOI: 10.1091/mbc.8.6.973
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar concentrations of nocodazole alter microtubule dynamic instability in vivo and in vitro.

Abstract: Previous studies demonstrated that nanomolar concentrations of nocodazole can block cells in mitosis without net microtubule disassembly and resulted in the hypothesis that this block was due to a nocodazole-induced stabilization of microtubules. We tested this hypothesis by examining the effects of nanomolar concentrations of nocodazole on microtubule dynamic instability in interphase cells and in vitro with purified brain tubulin. Newt lung epithelial cell microtubules were visualized by video-enhanced diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
328
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(355 citation statements)
references
References 47 publications
17
328
1
Order By: Relevance
“…To avoid the confounding effects that can be produced by the activity of these drugs in the other mitotic phases, control and CIT-K-depleted HeLa cells were synchronized and treated with the drugs during telophase, that is, after the genetic material had already been segregated by spindle microtubules. The drugs were used at a low concentration, which is known to specifically affect dynamic microtubules, 32,33 Conversely, we found that nocodazole treatment rescues the cytokinesis delay phenotype induced by CIT-K overexpression that we previously described 23 ( Figure 2f). Altogether, these results indicate that CIT-K regulates abscission by increasing the stability of midbody microtubules and that differential stability of dynamic microtubules during cytokinesis may determine the sensitivity of cells to CIT-K loss.…”
Section: Resultsmentioning
confidence: 47%
“…To avoid the confounding effects that can be produced by the activity of these drugs in the other mitotic phases, control and CIT-K-depleted HeLa cells were synchronized and treated with the drugs during telophase, that is, after the genetic material had already been segregated by spindle microtubules. The drugs were used at a low concentration, which is known to specifically affect dynamic microtubules, 32,33 Conversely, we found that nocodazole treatment rescues the cytokinesis delay phenotype induced by CIT-K overexpression that we previously described 23 ( Figure 2f). Altogether, these results indicate that CIT-K regulates abscission by increasing the stability of midbody microtubules and that differential stability of dynamic microtubules during cytokinesis may determine the sensitivity of cells to CIT-K loss.…”
Section: Resultsmentioning
confidence: 47%
“…Role of the cytoskeleton network The involvement of the cytoskeleton network in C-peptide endocytosis was studied in HAEC with cytochalasin D (30 mmol/l) and nocodazole (10 mmol/l), which act by inducing depolymerisation of actin filaments and microtubules, respectively [25,26]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Migratory cells form a stable sub-population of microtubules at the leading edge to reorient the microtubule organizing center (MTOC) between the nucleus and the leading edge to create a polarized microtubule array that directs vesicular trafficking and maintains cell shape [9,10,19]. Additionally, disruption of the microtubule network by nocodazole-induced microtubule catastrophe or taxol-mediated microtubule stabilization, results in a depolarized cell morphology and a dramatic reduction in both the rate and directionality of migration [2,20]. Conversely, release from the stabilizing effects of microtubule antagonists has been shown to induce microtubule regrowth toward the membrane ruffle, activation of Rac1 and the formation of filopodia and lamellipodia [2,19,21].…”
Section: The Cytoskeleton and Cellular Extensionmentioning
confidence: 99%
“…For example, nocodazole-induced microtubule depolymerisation leads to an increase in the number and size of focal adhesions at both the leading and trailing edge, anchoring the cell to the ECM to the point where it becomes immobilized [19]. Rescue of microtubule growth following catastrophe shows a resurgence in targeting events of focal adhesions by microtubule plus ends, resulting in focal adhesion dissolution and cell migration [2,19,20]. Microtubule plus ends have been shown to be differentially regulated depending on their subcellular location within the migrating cell.…”
Section: A) D) C) B) E)mentioning
confidence: 99%